Bibliometric review of improvements in building maintenance. Issue 4 (9th October 2017) - Rocha, Patricia; Rodrigues, Rui Calejo
Abstract : Purpose: The purpose of this paper is to review the status of knowledge on the subject of building maintenance from an integrated perspective that incorporates the building lifecycle, that is, from the design stage to the end of life. This work considered the main aspects to be taken into account in determining and implementing maintenance strategies, which requires a cross-sectional view of the entire construction process. At the same time, this approach contributes to the organisation of building management. Design/methodology/approach: Bibliometric review has been carried out to identify relevant subjects and topics about scientific production on building maintenance by analysing the contents of about 745 publications, over the last 15 years, between 2000 and 2016 (first quarter). The survey results were gradually organised into a database grouped into seven main themes which were found to be more discussed and others six emergent themes with topics on building maintenance research. Findings: This research enabled a synthesis of the focal points in the literature on building maintenance, as well as debates among researchers and institutions in the field. The result is a view to the future regarding what issues merit further research and what content requires greater depth of understanding, allowing us to envision research directions that encompass topics and sub-topics for future development. To this end, this bibliometric study draws on knowledge developed over the last 15 years, using research studies published in refereed journals indexed in ISI/SCOPUS as its data source. Originality/value: The novelty of this topic, and the aspect in which it differs from existing studies, is that the researchers analysed a single sub-topic: that is, content regarding maintenance. Thus, this bibliometric literature review allows us to achieve a comprehensive and integrated view of key issues developed in the field of building maintenance. The results show which topics have been more thoroughly developed and which still exhibit gaps and weaknesses. This review allows us to envision well thought out guidelines for future development that have the potential to be relevant to progress in building maintenance research. It also contributes to our understanding of the state of the art in this field of knowledge.